1989
DOI: 10.3354/meps056145
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase activity in tropical carbonate marine sediments

Abstract: Rates of nitrogenase acbvity were investigated in carbonate sediments of shallow tropical waters uslng the acetylene (C2H2) reduction method Nitrogenase achvlty was significantly h g h e r in fine grained sedments than m coarser grained sands The importance of oxygen, ammonium (NH:) and organic substrate availability in regulating nitrogenase activ~ty in these sedlments was evaluated The effect of O2 was vanable and appeared to be influenced by physical dsturbance of the sediment Ammonium did not appear to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…9, Table 1). Repression of nitrogenase activity by NH4+ is often variable in sedi m e n t~, both with and without vegetation, and may partly reflect differences in bacterial populations that vary in their susceptibility to NH4+ inhibition , O'Neil & Capone 1989. It is possible, however, that we did not observe NH4+ repression of nitrogen fixation in either the intact cores or sediment slurries because in situ nitrogen fixation activities were already below maximum rates because of the presence of NH,+ , and thus NH,' additions would be unlikely to further decrease nitrogen fixation rates.…”
Section: Discussionmentioning
confidence: 99%
“…9, Table 1). Repression of nitrogenase activity by NH4+ is often variable in sedi m e n t~, both with and without vegetation, and may partly reflect differences in bacterial populations that vary in their susceptibility to NH4+ inhibition , O'Neil & Capone 1989. It is possible, however, that we did not observe NH4+ repression of nitrogen fixation in either the intact cores or sediment slurries because in situ nitrogen fixation activities were already below maximum rates because of the presence of NH,+ , and thus NH,' additions would be unlikely to further decrease nitrogen fixation rates.…”
Section: Discussionmentioning
confidence: 99%
“…In coral reef ecosystems, N 2 fixation is conducted by various types of organisms, including symbiotic algae in coral; sponges; mat-forming and epiphytic algae; and microalgae in sediments (Weibe et al, 1975; York (1969). Iizumi, 1992;Crossland and Barnes, 1976;Corredor et al, 1988;Miyajima et al, 2001;O'Neil and Capone, 1989;Lesser et al, 2004). Yamamuro et al (1995) also reported 15 N-depleted macrophytes (δ 15 N~0‰) in the Palau reef, supporting N 2 fixation.…”
Section: Fig 2 (A) Spatial Profile Of δ 15 N Values At 900°c Step Wmentioning
confidence: 99%
“…In order to understand the mechanism of the high productivity, investigation of the nitrogen cycle within the coral reef ecosystem is essential, since nitrogen is one of the most important nutrients. Biogeochemical studies have suggested that one of the nitrogen sources for reef ecosystem is atmospheric nitrogen, which is assimilated by symbiotic algae in coral, sponges, mat-forming and epiphytic algae, and by microalgae in sediments (Weibe et al, 1975;Iizumi, 1992;Crossland and Barnes, 1976;Corredor et al, 1988;Yamamuro et al, 1995, Miyajima et al, 2001O'Neil andCapone, 1989, Lesser et al, Wright et al (1988) established a technique that enabled nitrogen isotopic ratios to be measured on subnanomole samples of molecular nitrogen. We have developed a similar system by using a modified noble gas mass spectrometer .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after first evidence of a diazotroph-coral association by Shashar and others (1994a) and the subsequent discovery of diazotrophic cyanobacteria in the tissue of scleractinian corals of the genus Montastraea (Lesser and others 2004), there has been emergent recognition of the potential contribution of N 2 -fixing symbioses in coral reefs (Fiore and others 2010;Cardini and others 2014). Although reef sediments and cyanobacterial mats show high rates of BNF (O'Neil and Capone 1989;Capone and others 1992;Shashar and others 1994b;CharpyRoubaud and others 2001;Bednarz and others 2015b), N 2 -fixing coral symbioses may also be responsible for significant inputs of N on the ecosystem level, particularly in reef habitats with high live coral coverage.…”
Section: Introductionmentioning
confidence: 99%